ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS SEKTOR PERDAGANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agusvinna, Agusvinna; Tipa, Handra (LPPM Universitas Putera Batam, 2022)
A trading company is a company that buys goods and resells them to gain a profit or profitability. The profit earned comes from the difference between purchase price and selling price. There are many factors that can affect the level of profitability. This research aims to study the affect of inventory turnover, receivable turnover and working capital turnover on profitability in trading companies that listed on Indonesia Stock Exchange for the period 2016-2020. This can be a consideration for the company to improve company’s performance and also investors as one of the factor in making decision to invest. The population consisted of 27 companies with the sample technique used was purposive sampling. The sample in this study were companies that met the criteria, there were 7 companies with 35 data. The data is collected using secondary data which is taken through the official website www.idx.co.id and processed using SPSS application (Statistical Product and Service Solution) version 25. Based on the results, simultaneous inventory turnover, receivable turnover dan working capital turnover have a significant effect of profitability. Partially, receivable turnover has an influence on profitability. Meanwhile, inventory turnover and capital working turnover partially do not have a significant effect on profitability of retail trading sub-sector trading companies that listed on Indonesia Stock Exchange.